Altered Neutrophil-to-Lymphocyte Ratio and Systemic Immune-Inflammation Index in Children with Breath-Holding Spells: A Retrospective Comparative Study - Günce Başarır; Rıdvan Avcı (Izmir Katip Celebi University Faculty of Medicine, 2026)
Objective: To evaluate whether complete blood count (CBC)-derived hematological and inflammatory indices differ between children with breath-holding spells (BHS) and a control group without neurological or chronic systemic disease, and whether laboratory parameters can contribute to distinguishing cyanotic and pallid subtypes. Materials and Methods: This retrospective, single-center comparative study included 47 children diagnosed with BHS (22 cyanotic, 25 pallid) and 50 controls without neurological, hematological, or chronic systemic disease. A complete blood count obtained at the diagnostic evaluation was available for 44 of the patients (21 cyanotic, 23 pallid) and for all 50 controls. CBC parameters, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) were compared, and multivariable logistic regression was used to adjust the main comparisons for age and sex. Within the BHS cohort, iron status, vitamin B12, and thyroid function parameters were compared between the cyanotic and pallid subtypes. Results: Children with BHS had a significantly lower absolute neutrophil count (p=0.001, q=0.006), NLR (p<0.001, q<0.001), and SII (p<0.001, q<0.001), and a higher absolute lymphocyte count (p=0.004, q=0.019) than controls. Both NLR and SII remained associated with BHS after adjustment for age and sex (adjusted odds ratio 0.93 per 0.1 unit of NLR, 95% CI 0.89-0.98, p=0.006; 0.81 per 100 units of SII, 95% CI 0.70-0.94, p=0.005). ROC analysis showed NLR was the strongest single discriminator for BHS (AUC 0.765, 95% CI 0.663-0.866; Youden cut-off ≤0.661; 68.2% sensitivity, 82.0% specificity). No individual biochemical parameter differentiated the cyanotic and pallid subtypes (all p>0.05). Conclusion: Children with BHS showed a shift in neutrophil-lymphocyte balance that differs from the pattern usually seen in inflammatory conditions and is compatible with, although not proof of, autonomic dysregulation. Given their moderate discriminatory performance, NLR and SII are best regarded as supportive laboratory parameters that may accompany the clinical assessment of BHS.